Electron Bifurcation and Confurcation in Methanogenesis and Reverse Methanogenesis - Yan, Zhen; Ferry, James G. (Frontiers in Microbiology, 2018)
Flavin-based electron bifurcation plays an essential role in the CO2 reduction pathway of methanogenesis. The first reaction in the pathway is the thermodynamically unfavorable ferredoxin-dependent reduction of CO2 with H2 or formate to formylmethanofuran and the final reaction is the thermodynamically favorable reduction of the heterodisulfide CoM-S-S-CoB with H2 or formate to coenzyme M (CoM-SH) and coenzyme B (CoB-SH). The two reactions are energetically coupled by the electron bifurcating heterodisulfide reductase (HdrABC), complexed with hydrogenase or formate dehydrogenase, catalyzing the CoM-S-SCoB-dependent reduction of ferredoxin with H2 or formate. A structural and functional variant of HdrABC (HdrA2B2C2) is proposed to play a role in the Fe(III)-dependent anaerobic oxidation of methane by catalyzing the bifurcation of electrons from reduced coenzyme F420 (F420H2) into ferredoxin and CoM-S-S-CoB in response to limiting concentrations of Fe(III). A role for electron confurcation by an HdrABC/FrhB complex is proposed for nitrate-dependent anaerobic oxidation of methane in which the endergonic oxidation of CoM-SH/CoB-SH and the exergonic oxidation of ferredoxin confurcate to the reduction of two F420. The F420H2 is substrate for the Fqo (F420H2 dehydrogenase) complex that generates a proton gradient driving ATP synthesis.